Investigating the Role of Guanosine on Human Neuroblastoma Cell Differentiation and the Underlying Molecular Mechanisms - Belluardo, Natale; Mudò, Giuseppa; Di Liberto, Valentina; Frinchi, Monica; Condorelli, Daniele F.; Traversa, Ugo; Ciruela, Francisco; Ciccarelli, Renata; Di Iorio, Patrizia; Giuliani, Patricia (Frontiers in Pharmacology, 2021)
Neuroblastoma arises from neural crest cell precursors failing to complete the process of differentiation. Thus, agents helping tumor cells to differentiate into normal cells can represent a valid therapeutic strategy. Here, we evaluated whether guanosine (GUO), a natural purine nucleoside able to induce differentiation of many cell types, may cause the differentiation of human neuroblastoma SH-SY5Y cells and the molecular mechanisms involved. We found that GUO, added to the cell culture medium, promoted neuron-like cell differentiation in a time- and concentration-dependent manner. This effect was mainly due to an extracellular GUO action since nucleoside transporter inhibitors reduced but not abolished it. Importantly, GUO-mediated neuron-like cell differentiation was independent of adenosine receptor activation as it was not altered by the blockade of these receptors. Noteworthy, the neuritogenic activity of GUO was not affected by blocking the phosphoinositide 3-kinase pathway, while it was reduced by inhibitors of protein kinase C or soluble guanylate cyclase. Furthermore, the inhibitor of the enzyme heme oxygenase-1 but not that of nitric oxide synthase reduced GUO-induced neurite outgrowth. Interestingly, we found that GUO was largely metabolized into guanine by the purine nucleoside phosphorylase (PNP) enzyme released from cells. Taken together, our results suggest that GUO, promoting neuroblastoma cell differentiation, may represent a potential therapeutic agent; however, due to its spontaneous extracellular metabolism, the role played by the GUO-PNP-guanine system needs to be further investigated.